WHAT CONSIDERATIONS SHOULD THE EFL/ESL TEACHER TAKE INTO ACCOUNT WHEN TEACHING VOCABULARY? - Sultan Baa (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2022)
As foreign language/second language (EFL/ESL) learners, vocabulary mastery is one of the important aspects of English. The centre of language teaching and important for language learners are aspects of vocabulary. Several studies have shown that teaching vocabulary can be considered a problem because some teachers are unsure about best practices in teaching and are not really aware of ways to initiate instructional vocabulary learning (Berne & Blachowicz, 2008). This article presents four aspects the EFL/ESL teacher might take into account when teaching vocabulary, namely: focus on frequent words, strategies for dealing with unknown words, lexical approach in teaching vocabulary, and semantic fields in vocabulary teaching.